Examining the empowering effect of femvertising from the corporate social responsibility perspective: a survey-based online experimental study in China - Feng, Ran (Frontiers in Communication, 2025)
Femvertising is a marketing communication strategy in which brands encourage and inspire women by incorporating information supporting them to gain profit and social impact. From the theoretical perspective of corporate social responsibility, this study tries to explore the empowering effects of femvertising exposure on Chinese female consumers. Through a survey-based online experiment on 300 respondents, the study found that femvertising can significantly enhance self-esteem and self-efficacy, but has no significant effect on self-control. For female-oriented products, consumers’ perception of female empowerment in femvertising is significantly higher than that in traditional advertisements, while there is no significant difference between the two for general product advertisements. The perception of female empowerment influences volunteering behavior intention related to women’s rights through a sense of moral elevation. This article expands the application of corporate social responsibility theory in the Chinese femvertising practices. It helps practitioners to evaluate better whether relevant marketing and communication activities strike a balance between commercial interests and social responsibility.